Social equity in climate-resilient agriculture - CGIAR; Nordic Africa Institute (2022)
The purpose of this Briefing Note is to assist the ClimBeR team and partners to frame issues of social equity in building resilience to climate variability and extremes. It identifies what social equity means, highlights why attention to social equity is important and provides a framework to explore different equity dimensions.